Penitence : a Novel - Koval, Kristin (New York : Celadon Books, 2025)
"When their thirteen-year-old daughter Nora kills her terminally ill brother, Angie and David Sheehan struggle to pick up the pieces of their shattered lives. They turn to small-town lawyer Martine Dumont for help, but Martine isn't just legal counsel-she's also the mother of Angie's ill-fated first love, Julian, a successful criminal defense attorney. Martine promptly draws him into the legal battle against an overreaching district attorney determined to try Nora as an adult."--
Keywords: Criminal defense lawyers -- Fiction; Families -- Colorado -- Fiction; First loves -- Fiction; Fratricide -- Fiction; Siblings -- Fiction; Terminally ill -- Fiction; Women lawyers -- Fiction; Colorado -- Fiction; New York (N.Y.) -- Fiction